Ultrasound-Guided In-Plane Subclavian Vein Puncture versus Prior Ultrasound and Landmark Technique: A Randomized Controlled Trial - Conrad, David; Schneider, Sven Oliver; Beller, Samira; Wagenpfeil, Gudrun; Volk, Thomas; Müller-Wirtz, Lukas M.; Meiser, Andreas (Anesthesia and analgesia, 2026)
BACKGROUND: Central venous catheterization (CVC) of the subclavian vein is a standard procedure in medicine. Ultrasound guidance is increasingly recommended to improve the success rates and reduce complications. This study compared the success rates and complications of ultrasound-guided microconvex in-plane subclavian puncture (MISP) with those of the landmark technique. METHODS: In this randomized controlled trial, 101 patients scheduled for elective surgery were enrolled and randomly assigned to either the group MISP or the control group using the landmark technique after ultrasound prescan. The primary end point was an a priori defined composite risk score including puncture attempts, required time, posterior venous wall injury, arterial punctures, hematoma formation, hemo-, pneumothorax, and catheter mispositioning. The secondary and exploratory end points included success rates, complication rates, and procedural times. Comparisons between groups were performed using Student t test, χ2 test, and Mann-Whitney U test with a significance level of 0.05. Data are mean ± standard deviation [SD], frequencies (%) or 95% confidence interval [CI] [lower limit-upper limit]). RESULTS: The mean ± SD composite risk score was significantly lower in the MISP group compared to control (6.4 ± 5.9 vs 11.6 ± 10.8; mean diff 5.21 [95% CI, 1.71-8.71], P = .028). The MISP technique demonstrated significantly higher as-treated overall success rates (86% [95% CI, 74.6%-93.9%] vs 71% [95% CI, 56.2%-82.5%], P = .046) and significantly reduced the risk of arterial punctures (1.9% [95% CI, 0.05%-10.45%] vs 12% [4.5%-24.3%], number needed to harm: 10 punctures, P = .047). One pneumothorax was noted in both groups (2% each). The mean procedural time was 5 minutes longer in the MISP group (P < .001). CONCLUSIONS: Compared with the landmark technique, the ultrasound-guided MISP technique significantly reduced the risk of complications. The extended procedural time may be justified by lower complication rates. Further studies should evaluate the implementation of the MISP technique as a standard approach for subclavian vein catheterization.
CRIS-Team Scopus Importer:2026-04-24